Kaimo kultūrinio kraštovaizdžio vertė - Jurevičienė, Jūratė (Journal of Architecture and Urbanism, 2010)
Cultural value of agrarian landscape The paper discusses changes of the concept of cultural value of agrarian landscape in a few last decades. The interaction of the community and landscape, urgent problems of assessment and treatment of cultural landscape in rural areas of today’s Lithuania are revealed. Recent changes in the understanding of the value and shifts in the contents of this concept require improvement of the legal system of Lithuania on a few levels. Contradictions in the system of listing in the context of low efficiency of urban heritage preservation and economic decline are analysed. Inadequate role of local communities is revealed as one of the basic factors of threats to authenticity of relict agrarian landscapes. Recent international documents on cultural landscape protection enable perfection of this heritage preservation. Article in Lithuanian. Santrauka. Nagrinėjamos kaimo kultūrinio kraštovaizdžio problemos, susijusios su jo vertės sampratos kaita pastaraisiais dešimtmečiais Vakarų šalyse ir Lietuvoje. Atskleidžiami mažai nagrinėti Lietuvos kaimo kraštovaizdžio vertės aspektai. Siekiama atskleisti dabartinėje Lietuvos kaimiškojo kraštovaizdžio reglamentavimo sistemoje slypinčius pavojus jo vertingosioms savybėms išlikti. Lyginami reikalavimai, nustatyti šiuose dokumentuose ir Lietuvos ratifikuotuose Europos Sąjungos teisės aktuose. Lyginama vietos bendruomenių sąsajų su kraštovaizdžiu svarba ir ribotos teisinės bei ūkinės prielaidos joms dalyvauti kaimiškojo kultūrinio kraštovaizdžio vertės nustatymo ir jos išsaugojimo procesuose. Reikšminiai žodžiai: kultūrinė vertė, aplinkos kūrimo tradicijos, kaimo kraštovaizdis, Dieveniškių regioninis parkas. First Published Online: 22 May 2013